Novel structural features and phase transition behaviour of (Sr1-xCax)TiO3: II. X-ray diffraction studies - Ranjan R.; Pandey D. (My University, 2025)
Results of a careful XRD study of the room temperature structure of (Sr1-xCax)TiO3 (SCT) with 0.0 ≤ x ≤ 1.0 are presented to show that the structure of SCT is CaTiO3- (CT-) like for x ≥ 0.12. High temperature XRD studies on the phase transition behaviour of SCT with 0.12 ≤ x ≤ 0.21 show the existence of an intermediate phase in between the room temperature orthorhombic phase and the high temperature cubic phase. This is analogous to the phase transition behaviour of pure CT and is attributed to the softening of the R25 and M3 point phonon modes. © 1999 IOP Publishing Ltd.